Fe3O4@chitosan Microspheres Coating as Cytoprotective Exoskeletons for the Enhanced Production of Butyric Acid With Clostridium tyrobutyricum Under Acid Stress - Liu, Tingting; Jiang, Cheng; Zhu, Liying; Jiang, Ling; Huang, He (Frontiers in Bioengineering and Biotechnology, 2020)
The introduction of inorganic nano-materials may endow microbial cells with unique new features, including greater resistance to adverse abiotic stress. The aim of this work was to enhance the acid tolerance of C. tyrobutyricum ATCC 25755 by coating cells with self-assembled Fe3O4@chitosan (Fe3O4@CS) microspheres, and thereby increase the production of butyric acid. The optimal coating efficiency of 81.19 % was obtained by systematically optimizing the three operational parameters temperature, rpm and mass ratio, which were determined to be 37 °C, 80 rpm and 1:2, respectively. Physicochemical characterization was used to assess the superparamagnetism, thermostability and subsize of Fe3O4@CS attached to the cells. Compared to free cells, C. tyrobutyricum coated with Fe3O4@CS (CtFC) exhibited stronger acid tolerance at low pH. At a pH of 4 or 5, the levels of ROS, MDA, LDH and SOD caused by the acid environment in free cells were significant higher than in CtFC. Moreover, without adding NaOH, CtFC fermentation showed a higher butyric acid titer (37.60 vs 31.56 g/L) compared to free-cell fermentation. At the same time, an average butyric acid yield of 0.46 g/g in each repeated-batch fermentation was also obtained by taking advantage of the biocatalyst’s reusability and convenient separation from the fermentation broth via an external magnetic force. Overall, the developed CtFC illustrates a new paradigm for developing an economical and reusable biocatalyst for industrial application in butyric acid production.